Probing thermal decomposition mechanism of molten nitrite/nitrates salt by time of flight mass spectrometry. (1st May 2019) - Fei, Zejie; Zhang, Yu; Ge, Min; Wang, Yongtian; Li, Yanli; Cheng, Jinhui; Wei, Baoren; Hou, Huiqi; Liu, Hongtao
Highlights: The thermal stability of nitrate/nitrite salt was studied by TOF-MS. Nitrate/nitrite salts decompose via superoxide and peroxide ion formation. The thermal decomposition mechanism was proposed below 300 °C. Abstract: A time of flight mass spectrometer (TOF-MS) combined with a specially designed in-situ heating furnace was used for analyzing gaseous products evolved during salt decomposition. The thermal decomposition behavior of solar salt (60 wt% NaNO3 –40 wt% KNO3 ) and sodium nitrite at temperature above melting point was investigated. According to mass spectra recorded at different temperature, both solar salt and sodium nitrite thermally decomposed above their melting point and the main products are NO and N2 respectively. An unusual N2 O was also observed in gaseous products by TOF-MS, while no O2 or NO2 was found at temperature bellow 300 °C. The result shows a very different reaction process from the common sense that O2 or NO2 should exist in the decomposition process. Based on these new evidences, the thermal decomposition mechanism of molten nitrite/nitrates salt is proposed, which suggests that there should be intermediate state such as superoxide and peroxide ions in the molten salt in the initial thermal-chemical reaction process.